Synovial calprotectin: A potentially useful biomarker for the diagnosis of Kingella kingae native arthritis - Anne‐Gaëlle Leroy; Pascale Bémer; Cyrille Decante; Louise Ruffier d’Epenoux; Eve Tessier; Vincent Crenn; Aurélie Guillouzouic; Stéphane Corvec; The CRIOGO Microbiology Study Group (Clinical Case Reports)
Abstract Kingella kingae is a bacteria involved in developing arthritis in children. Its diagnosis remains difficult. We report a case for which a new biomarker, calprotectin measured in the synovial fluid, was strongly positive and a specific molecular test was the only way to diagnose it specifically.